The Discursive Construction of Identities On- and Offline Personal - group - collective - Bös, Birte; Kleinke, Sonja; Mollin, Sandra; Hernández, Nuria (John Benjamins Publishing Company, 2018)
This volume explores linguistic identity construction across online and offline contexts. The contributors focus on 'clusivity' as an overarching aspect and offer a multifaceted operationalisation of the linguistic processes of identity construction. The studies address three major strands of human identity, each of which can be thought of as an aggregative abstraction with its own complexities: personal identity, group identity and collective identity. The contributions pay special attention to the interplay between the public and private dimensions of the interactions and audiences, as well as the potential impact of social and technical affordances of different communicative settings and online and offline modes of identity construction. The volume is aimed at all researchers concerned with the complex notion of identity, both in linguistics and in neighbouring disciplines.